Increased Cholesterol Levels and Age in Housewives - Fajar Husen; Nuniek Ina Ratnaningtyas; Nur Aini Hidayah Khasanah; Nilasari Indah Yuniati (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2022)
Introduction; Cholesterol is a metabolite of fat that contains sterol compounds and is mostly concentrated in cell membranes in the body and the circulatory system. Purpose; Knowing total cholesterol levels in housewives (IRT) based on the age range category of 25 - 80 years and the relationship between increasing total cholesterol levels with the age of IRT. Method; The research method is analytical descriptive with a corss-sectional method approach, with a total sample of 30 and the sampling technique is purposive sampling method. Data on the relationship between total cholesterol levels and age were statistically analyzed by bivariate analysis with the Pearson correlation index on SPSS software. Results; The results showed that the average IR cholesterol level was 198.07 mg/dL, and the average age was 47.87 years. There are 50% of respondents who have good cholesterol levels, 26.67% in the border category, and 23.33% in the danger category with the highest cholesterol levels being 297 mg/dL and the lowest being 130 mg/dL.Conclusion; Total cholesterol levels in IRT in Tanjung Village, South Purwokerto showed that there was a strong relationship between increased cholesterol levels in the body and increasing age